Analisis Kandungan Oksida Logam Clay Alam Kabupaten Pangkep Provinsi Sulawesi Selatan sebagai Bahan Dasar Pembuatan Keramik Berpori Gelcasting - Suriati Eka Putri; Abdul Rahman; Diana Eka Pratiwi; Ahmad Fudhail Majid; Rachmat Triandi Tjahjanto (Jurnal Kimia Fullerene, 2021)
The purpose of this study was to analyze the metal oxide content in natural clay in Pangkep Regency, South Sulawesi Province, which will be used as the basic material for making gelcasting porous ceramics. One of the basic ingredients for making ceramics is alumina silica metal oxide. This metal oxide is found in several minerals, one of which is clay minerals. The sample used in this study was natural clay in Pangkep Regency, South Sulawesi Province. The parameters studied were alumina silica content before and after natural clay was used in the synthesis of porous ceramics. The synthesis method used is the gelcasting method. The metal oxide content was analyzed using XRF and to observe the morphology of the ceramic body using SEM. The results showed that the metal oxide content for the main ceramic material in the form of alumina silica did not change significantly before and after sintering, Al2O3 was 11.98% before sintering and 11.32% after sintering while SiO2 content was 71.12% before sintering and 73.32% after sintering. It is supported by the results of the morphology of the ceramic body, natural clay that has undergone curing in the ceramic body.